Intellectual property rights in the European Unian and the evolution of trademarks together with the exhaustion of rghts prrinciple in scope Customs Unian - Güdüm, Sinem (My University, 1998)
unknown
Keywords: Hakların Tüketilmesi; Marka; Marka Hakkı; Mülkiyet Hakkı